Bitcoin mining: converting computing power into cash flow. Issue 14 (16th August 2019) - Lo, Yuen C; Medda, Francesca
ABSTRACT: Bitcoin is the world's leading cryptocurrency, with a market capitalization briefly exceeding 300 billion. This hints at Bitcoin's amorphous nature: Is this a monetary or a corporate measure? Hard values become explicit in the processing of transactions and the digital mining of Bitcoins. Electricity is a primary input cost. Bitcoins earned are often used to circumvent local currency controls and acquire US dollars. For the period August 2010 to February 2018, we examine the financial components of Bitcoin mining revenues, their statistical contribution to daily changes, and to its variance. We provide empirical evidence that Bitcoin transaction processing is capacity constrained.